Un’alleanza possibile. Un cohousing sociale per giovani nativi e stranieri - Bosis, Federico (Antropologia Pubblica, 2024)
Co-housing in Italy is a living arrangement that provides young people with a measure of autonomy in a context marked by increasingly pressing socio-economical circumstances. In particular, this article examines a co-housing project where young Italians live together with unaccompanied underage migrants. This article contextualizes the contemporary experience of young people within the extensive socio-economical and affective-relational changes that affected Italy and the West in the past decades, precarizing life choices, as well as the possibility to plan for the future and adult life. In this context, I trace both the material and the symbolic relevance of housing and habitation as a complex practice, which shapes the subject’s ability to relate to the world and to act in it. Expanding on this, I have looked into the structuring and the development of a specific co-housing project. The results of this study allow me to consider housing and peer co-housing as a particularly fruitful context for the development of an educational project that aims to consider the differences between young locals and young migrants. At the same time, this context reveals a degree of approximation between different experiences of growth in a globalized world. On the other hand, the ethnographic attention applied to the context also allows to point out the risks that such an educational project might entail.